Diagnostic and Prognostic Impact of Progesterone Receptor Immunohistochemistry: A Study Evaluating More Than 16, 000 Tumors. (8th August 2022) - Viehweger, Florian; Tinger, Lisa-Marie; Dum, David; Gorbokon, Natalia; Menz, Anne; Uhlig, Ria; Büscheck, Franziska; Luebke, Andreas M.; Hube-Magg, Claudia; Hinsch, Andrea; Höflmayer, Doris; Fraune, Christoph; et al.
Abstract : Progesterone receptor (PR) is a member of the nuclear/steroid hormone receptor family of ligand-dependent transcription factors. It plays an important role in reproduction and mammary gland development and has various tissue-specific effects in nonreproductive organs. In diagnostic pathology, positive PR immunostaining is used to support a diagnosis of breast or gynecologic origin in a tumor. In this study, the expression of PR was analyzed by immunohistochemistry in 18, 176 (interpretable: 16, 445) samples from 147 different tumor types and subtypes in a tissue microarray format. PR immunostaining was detected in 57.4% of breast tumors, 28.6% of other gynecological tumors, and 1.8% of nongynecological and nonmammary tumors. Among the group of nongynecological and nonmammary tumors, particularly high rates of PR positivity were seen in neuroendocrine tumors (54.3%) and neuroendocrine carcinomas (35.7%) of the pancreas. A comparison with clinico-pathological parameters showed that reduced PR immunostaining was significantly associated with adverse histopathological and clinical features in breast carcinoma, endometrioid endometrial carcinoma, and pancreatic neuroendocrine tumors. In summary, our analysis of 147 different tumor types for PR immunostaining provides a ranking list of tumor entities according to their prevalence of PR positivity, helps to better understand the diagnostic utility of PR, and highlights the distinct PR positivity among neuroendocrine neoplasms of pancreatic origin.